1999
DOI: 10.1007/s11357-999-0006-3
|View full text |Cite
|
Sign up to set email alerts
|

Age-associated decreases in human DNA repair capacity: Implications for the skin

Abstract: Multiple pathways are involved in accurate synthesis and distribution of DNA during replication, repair and maintenance of genomic integrity. An increased error rate, abovethe spontaneous mutation baseline, has been implicated in carcinogenesis and aging. Moreover, cytogenetic abnormalities are increased in Down's, Edwards', Patau's, and Klinefelter's syndromes with increasing maternal age, and in Marfan's and Apert's syndromes with paternal age. In response to DNA damage, multiple overlapping systems of DNA r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 149 publications
1
4
0
Order By: Relevance
“…Most, if not all, of these protective responses were accomplished through induction of p53 (33–35). Furthermore, three different model systems demonstrated that pretreatment with pTT before UV irradiation reduced subsequent mutation frequency, in agreement with the demonstrated enhanced DNA repair (36–38). These studies were expanded to an ex vivo model (39) where pTT was shown to increase pigmentation, inhibit cell proliferation and speed the removal of UVR‐induced cyclobutane pyrimidine dimers in human skin.…”
Section: Oligonucleotides and Skin Photoprotectionsupporting
confidence: 75%
“…Most, if not all, of these protective responses were accomplished through induction of p53 (33–35). Furthermore, three different model systems demonstrated that pretreatment with pTT before UV irradiation reduced subsequent mutation frequency, in agreement with the demonstrated enhanced DNA repair (36–38). These studies were expanded to an ex vivo model (39) where pTT was shown to increase pigmentation, inhibit cell proliferation and speed the removal of UVR‐induced cyclobutane pyrimidine dimers in human skin.…”
Section: Oligonucleotides and Skin Photoprotectionsupporting
confidence: 75%
“…Telomerase expression may lower the risk of malignant transformation by stabilizing the genome [1], either via DNA repair or by preventing telomere ends from being recognized as double stranded breaks by DNA repair mechanisms, although the length of telomere (rather than telomerase expression per se) may be the defining factor. A number of studies [74][75][76] support the consensus that DNA repair declines with age [77]. In a number of diseases, it is telomere lengthening and the prevention of cell senescence that improves chromosome stability [78,80], not vice versa, suggesting that longer telomeres may be essential to chromosomal stability [84].…”
Section: Safety: Theorymentioning
confidence: 99%
“…As concerns about longevity increase, many research studies have investigated longevity using model organisms to understand the association between genetic contribution and lifespan [ 23 , 24 , 26 , 41 43 ]. However, human lifespan is too complex to clearly elucidate its biological and sociocultural factors.…”
Section: Healthy Traits Of Long-lived Populationmentioning
confidence: 99%